Toxicity assessment of pollutants sorbed on environmental sample microplastics collected on beaches: Part I-adverse effects on fish cell line. (May 2019) - Pannetier, Pauline; Cachot, Jérôme; Clérandeau, Christelle; Faure, Florian; Van Arkel, Kim; de Alencastro, Luiz F.; Levasseur, Clément; Sciacca, Frédéric; Bourgeois, Jean-Pascal; Morin, Bénédicte
Abstract: Microplastics (MPs), are tiny plastic fragments from 1 μm to 5 mm generally found in the aquatic environment which can be easily ingested by organisms and may cause chronic physical but also toxicological effects. Toxicological assays on fish cell lines are commonly used as an alternative tool to provide fast and reliable assessment of the toxic and ecotoxic properties of chemicals or mixtures. Rainbow trout liver cell line (RTLW-1) was used to evaluate the toxicity of pollutants sorbed to MPs sampled in sandy beaches from different islands around the world during the first Race for Water Odyssey in 2015. The collected MPs were analyzed for polymer composition and associated persistent organic pollutants: polycyclic aromatic hydrocarbons (PAHs), polychlorobiphenyls (PCBs) and dichlorodiphenyltrichloroethane (DDT). In addition, DMSO-extracts from virgin MPs, MPs artificially coated with B[a]P and environmental MPs were analyzed with different bioassays: MTT reduction assay (MTT), ethoxyresorufin-O-deethylase (EROD) assay and comet assay. Microplastics from sand beaches were dominated by polyethylene, followed by polypropylene fragments with variable proportions. Organic pollutants found on plastic from beach sampling was PAHs (2–71 ng g −1 ). Samples from Bermuda (Somerset Long Bay) and Hawaii (Makapu'u) showed the highest concentration of PAHs and DDT respectively. No toxicity was observed for virgin microplastics. No cytotoxicity was observed on cells exposed to MP extract. However, EROD activity was induced and differently modulated depending on the MPs locations suggesting presence of different pollutants or additives in extract. DNA damage was observed after exposure to four microplastics samples on the six tested. Modification of EROD activity level and DNA damage rate highlight MPs extract toxicity on fish cell line. Graphical abstract: Image 1 Highlights: Environmental MPs mostly composed by PE or PP according to different beaches. PAHs are detected on microplastic surface depending on location. Virgin industrial microplastic extract has no toxic effect on fish cell line. B[a]P coated extracts increase EROD activity and DNA damage. Environmental MP extracts show different toxicity profiles according to sites. Abstract : This study demonstrated the toxicity of environmental MP extracts on fish cells.